Analisis Kinerja Keuangan Pada PT. Telekomunikasi Indonesia Tbk Tahun 2020-2022 - Selmiati Tiranda; Elisabet Pali; Adriana M. Marampa (Jurnal Ekonomi dan Pembangunan Indonesia, 2023)
This study aims to analyze the financial performance of PT Telekomunikasi Indonesia Tbk during the 2020-2022 period in terms of liquidity, solvency, activity and profitability ratios. The type of research used is descriptive quantitative research. The type of data used is quantitative data and the data source used is secondary data. The data analysis technique used in this study uses financial ratios. The results of the study show that the financial ratios of PT Telekomunikasi Indonesia Tbk during the period studied show unfavorable performance. The liquidity ratio shows that the company has not maximized its short-term obligations. The solvency ratio shows that the company has the ability to fulfill its long-term obligations. The activity ratio indicates that the company has not been able to utilize and manage its assets to increase sales. Profitability ratios based on ROA and ROE analysis in unfavorable conditions indicate that the company has not maximized in generating satisfactory profits and has not been efficient in the use of capital and returns on net income on capital invested by the company owner. But the NPM analysis shows that the company is able to generate good profits.